Transcriptome profiles of organ tissues from pigs experimentally infected with African swine fever virus in early phase of infection - Sang-Ik Oh; Sheet, S.; Vuong Nghia Bui; Duy Tung Dao; Ngoc Anh Bui; Tae-Hun Kim; Cha, J.; Mi-Rim Park; Tai-Young Hur; Young-Hun Jung; Kim, B.; Hu Suk Lee; et al. (Informa UK Limited, 2024)
African swine fever, caused by African swine fever virus (ASFV), is a highly contagious and fatal disease that poses a significant threat to the global pig industry. The limited information on ASFV pathogenesis and ASFV–host interactions has recently prompted numerous transcriptomic studies. However, most of these studies have focused on elucidating the transcriptome profiles of ASFV-infected porcine alveolar macrophages in vitro. Here, we analyzed dynamic transcriptional patterns in vivo in nine organ tissues (spleen, submandibular lymph node, mesenteric lymph node, inguinal lymph node, tonsils, lungs, liver, kidneys, and heart) obtained from pigs in the early stages of ASFV infection (1 and 3 d after viremia). We observed rapid spread of ASFV to the spleen after viremia, followed by broad transmission to the liver and lungs and subsequently, the submandibular and inguinal lymph nodes. Profound variations in gene expression patterns were observed across all organs and at all time-points, providing an understanding of the distinct defence strategies employed by each organ against ASFV infection. All ASFV-infected organs exhibited a collaborative response, activating immune-associated genes such as S100A8, thereby triggering a pro-inflammatory cytokine storm and interferon activation. Functional analysis suggested that ASFV exploits the PI3K-Akt signalling pathway to evade the host immune system. Overall, our findings provide leads into the mechanisms underlying pathogenesis and host immune responses in different organs during the early stages of infection, which can guide further explorations, aid the development of efficacious antiviral strategies against ASFV, and identify valuable candidate gene targets for vaccine development.